Báo cáo tóm tắt Thẩm tra dự án Luật Quản lý, bảo vệ công trình quốc phòng và khu quân sự. - Ủy ban Quốc phòng và An ninh (2023)
Toàn văn Báo cáo tóm tắt Thẩm tra dự án Luật Quản lý, bảo vệ công trình quốc phòng và khu quân sự.